The Effectiveness of Duolingo Application to Enhance Students’ English Vocabulary Achievement at SMA Mambaus Sholihin 2 Blitar - Intan Susana; Zuraida .; Riski Amsari Saragih (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research aim to identify the teaching strategy was used by teacher in motivating students to learn English vocabulary. The researchers investigated the effectiveness of Duolingo application to enhance students' English vocabulary achievement at SMA Mambaus Sholihin 2 Blitar. It was conducted in one class of senior high school with consist of thirty-two students. This research applied a pre-experimental research design that was one group pretest and posttest. while the data that were derived from qualitative and quantitative data. The result showed that students’ mean score enhance from 61.15 up to 77.25. The hypothesis was analyzed at the significant level of 0.05, and the result showed that t-value was 16.10 and the sig.2-tailed 0.000. It means that hypothesis was accepted and found that Duolingo Application can be used in vocabulary teaching. Studies have shown that using Duolingo can lead to increased vocabulary scores and enhanced English language proficiency, suggesting that the application's features, like interactive lessons and point-based progress, can give motivation and engagement for English vocabulary achievement in classroom. Duolingo Application has motivated the students to practice of a foreign language by phone or computer easily. Overall, the study suggest that Duolingo is a game application that can be a valuable tool for enhancing their new vocabularies in the context at SMA Mambaus Sholihin 2 Blitar, potentially by boosting motivation and promoting consistent learning habits